2018
DOI: 10.5498/wjp.v8.i3.88
|View full text |Cite
|
Sign up to set email alerts
|

Drinking plain water is associated with decreased risk of depression and anxiety in adults: Results from a large cross-sectional study

Abstract: AIMTo investigate the relation between plain water drinking and risk of depression and anxiety among a large sample of Iranian adults.METHODSA total of 3327 Iranian general adults were included in this cross-sectional study. Validated Iranian version of the Hospital Anxiety and Depression Scale was used to assess anxiety and depression. Water consumption was assessed by asking about the number of glasses of water that consumed daily. Water consumption was categorized into < 2, 2-5, and ≥ 5 glasses of water/d.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…It is known that the consumption of fruits and vegetables may have a positive effect on general mental health, as it may promote higher levels of optimism and self-efficacy, reduce psychological distress, and protect against depressive symptoms [ 85 ]. Similarly, water intake may contribute to a decreased risk of depression and anxiety [ 86 ]. Taking this into account, it can be assumed that the observed changes in dietary behaviors are beneficial, as they may promote not only the physical but also the mental well-being of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the consumption of fruits and vegetables may have a positive effect on general mental health, as it may promote higher levels of optimism and self-efficacy, reduce psychological distress, and protect against depressive symptoms [ 85 ]. Similarly, water intake may contribute to a decreased risk of depression and anxiety [ 86 ]. Taking this into account, it can be assumed that the observed changes in dietary behaviors are beneficial, as they may promote not only the physical but also the mental well-being of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with the statement of Haghighatdoost (2018) who examined the relationship between water consumption with the risk of depression and anxiety in adults in Iran. 21 In his research, he did not find any relationship between the frequency of water consumption with the risk of depression. Stevenson (2016) also found that the increase in water quality and quantity did not have any correlation with psychological stress in women.…”
Section: Discussionmentioning
confidence: 91%
“…Some evidence suggests that fruit, vegetable, coffee, water, and moderate alcohol consumption are protective factors for MDD [10, 11, 12, 13, 15, 17]; but several other studies have failed to replicate these associations [6, 7, 8, 9, 19]. Considering potential residual bias, insufficient power, and a lack of temporality in cross-sectional studies, a carefully designed study with a large sample size, such as an MR study, is therefore required to help resolve this controversial issue.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, alcohol consumption was shown to be associated with increased risk of MDD in some studies [6, 7, 8, 9] but not in the others [10, 11, 12]. Several other potential protective factors for MDD were identified through randomized controlled trials and observational studies, including coffee and caffeine intake [13], omega-3 polyunsaturated fatty acid intake [14], fruit and vegetable intake [15], frequent fish consumption [16], plain water intake [17], and decreased fat intake (with induced body weight loss) [18]. However, there were also studies showing null association of MDD with consumption of tea and coffee [19], as well as fish [20].…”
Section: Introductionmentioning
confidence: 99%